Discrimination? Protestantism and Jewish Christians in the State of Israel - Van Klinken, Gert J (Stellenbosch Theological Journal, 2018)
During the nineteenth and early twentieth century, Jewish mission became an established branch of Protestant mission in general. As the Jewish converts to Protestantism remained fairly few in numbers, these converts were expected to engage in missionary efforts too, among their fellow Jews. One of the results of the ensuing polarization was the exclusion of baptized Jews from the citizenship of the State of Israel, where they were considered traitors by a majority of society. This article argues that programmes for Jewish-Christian dialogue in the State of Israel came under pressure to bar the Jewish Christians from taking part, and explores the question whether the ensuing policies can be ranked as examples of discrimination against this group.